Peer Tutoring: an Effective Solution For Learning Al-Qur'an Memorization at Al-Azhar Islamic Elementary School, Kemandoran: Penelitian - Siti ‘Aisyatunnadiya; Anwar Sanusi (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to measure the effectiveness of learning Tahfidz Al Qur'an through peer teaching at Al Azhar 5 Islamic Elementary School, South Jakarta. This research was used to obtain data using a case study qualitative method in class IIIC students of Tahfidz Al-Qur'an Learning Through Peer Tutors. In this study, researchers used one class to apply the Peer Tutor learning model, namely class III Mina, with a total of 26 students.The results of this study indicate that the use of peer tutoring practices in Quran memorization learning at SD Islam Al Azhar 5 Kemandoran has shown very positive results. This method not only improves students' memorization abilities but also contributes to the development of their character and social skills. By combining elements of teaching, social interaction, and effective time management, this program is an innovative and beneficial learning model. This opens up opportunities for implementing similar methods in other schools, exploring students' potential not only as individual learners, but as part of a mutually supportive learning community. Through this method, religious education is expected to have a broader and deeper impact on students, strengthening religious values, and preparing them to face future challenges. The peer guidance method effectively improves students' memorization of the Quran, character, and faith through a supportive learning community.